Knowledge, attitude and practices of contraception among the married women of reproductive age group in urban slums of Lucknow - Verma, Neeti; Bajpai, Prashant K. (International Journal of Research in Medical Sciences, 2021)
Background: Despite the availability of a wide range of contraceptive and mass media campaigns and information, education, and communication programs, population control remains a distant dream to achieve. The low use of spacing methods is reflected by early childbearing and short birth intervals. The present study was undertaken to assess the knowledge, attitude, and practice of different contraceptive methods among married women in the reproductive age group. Methods: A cross-sectional study was conducted among 230 married women in the reproductive age group (18-49 years) attending the outpatient department (OPD) of urban health training centre and came mainly from the neighboring slum locality. Results: We have included a total of 230 participants in the study analysis. Almost all (98.6%) of the study participants had knowledge about at least one method of contraception. If we see the use of contraceptive methods, 163 (70.8%) women ever used any of the contraceptive methods. Less than half (40.9%) had knowledge that contraceptive methods reduce the economic burden on the family. A negative attitude towards the practice of contraception was found among 11.7 percent of women in the study. When asking about present (last 1 year) practice of contraception, 29.1% not practiced any method of contraception, 25.6% used oral contraceptive pills (OCPs), and 27.8% used condoms. Conclusions: The study reveals good knowledge and favorable attitude of rural couples towards contraception. Contraceptive knowledge and practice were influenced by exposure to family planning messages. Women's education and counselling of couples can play an important role in adopting family planning methods.